Substitutability between drugs, innovation and growth in the pharmaceutical industry - Mello-Sampayo, F. de.; Vale, S. de S.; Camões, F. (10th EBES Conference Proceedings, 2013)
This paper establishes a relationship between the elasticity of demand for pharmaceutical intermediates and the growth rate for these intermediates variety. We build a model that contains two sectors, one final good sector producing treatments, and one intermediate goods sector producing a differentiated input used in the final treatment. The effects on the medicaments varieties' growth rate of the introduction of a fiscal instrument over pharmaceutical producers' profits are discussed. When the fiscal instrument is a tax over intermediate firms' profits, R&D by firms in the pharmaceutical goods sector results in positive growth provided there is enough substitutability among intermediates assured by a patent system. Otherwise, a subsidy over pharmaceutical firms' profits should be considered to generate positive growth of innovation in medicaments.